2021
DOI: 10.1080/21655979.2021.1924545
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox A5 activates p53 pathway to inhibit proliferation and promote apoptosis of adrenocortical carcinoma cells by inducing Aldo-Keto reductase family 1 member B10 expression

Abstract: 2021) Homeobox A5 activates p53 pathway to inhibit proliferation and promote apoptosis of adrenocortical carcinoma cells by inducing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…AKR1B10 is decreased in colorectal cancer tissue and AKR1B10 knockdown facilitates proliferation and migration of colorectal cancer cells ( 27 ). AKR1B10 suppresses cell viability and colony formation while facilitating apoptosis of NCI-H295R cells ( 7 ). In the present study, the knockdown of AKR1B10 weakened the effect of FNDC5 overexpression on proliferation, invasion, migration, EMT and apoptosis of NCI-H295R cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AKR1B10 is decreased in colorectal cancer tissue and AKR1B10 knockdown facilitates proliferation and migration of colorectal cancer cells ( 27 ). AKR1B10 suppresses cell viability and colony formation while facilitating apoptosis of NCI-H295R cells ( 7 ). In the present study, the knockdown of AKR1B10 weakened the effect of FNDC5 overexpression on proliferation, invasion, migration, EMT and apoptosis of NCI-H295R cells.…”
Section: Discussionmentioning
confidence: 99%
“…Aldo-keto reductase family 1 member B10 (AKR1B10), which belongs to the AKR superfamily, consists of 316 amino acids and its gene is located on chromosome 7q33( 6 ). AKR1B10 stimulation suppresses ACC cell proliferation and promotes apoptosis ( 7 ). BioGRID ( 8 ) predicted a potential interaction between fibronectin type III domain-containing protein 5 (FNDC5) and AKR1B10.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, the 1 × 10 7 ESCC cells were cross-linked with 1% formaldehyde and resuspended in lysis buffer [ 20 ]. The cell lysates were sonicated on ice, and the average length for DNA fragment was 500 bp.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Shuang (2015) found that removal of P21 knockout can directly accelerate the deterioration of liver cancer [37]. P21 is an inhibitor of cyclin-dependent kinase and multiple studies demonstrated a tumor suppressive role of P21 in tumorigene-sis [38,39]. The main mechanism of P21 to prevent cell cycle progression is to inhibit the expression of CCNE1 and PCNA, thereby reducing the expression of tumor growth factor and blocking the progress of cell cycle [40][41][42].…”
Section: Mechanisms Of Scs Inhibited Colorectal Cancer 291 Scs Inhibits the Growth Of Ht-29 By Regulating The Expression Of Genes Involvementioning
confidence: 99%